Assessment of drought variability using SPEI under observed and projected climate scenarios over Uttar Pradesh, India - Gond S.; Gupta N.; Dikshit P.K.S.; Patel J. (My University, 2025)
Drought is a widely occurring natural extreme that causes more severe negative impacts in the continuation of changing climate. This study presents the assessment of drought variability based on the standardized precipitation evapotranspiration index (SPEI) under historic and projected future climate scenarios. A probabilistic approach run theory is applied to define drought based on SPEI drought events, severity, intensity, and frequency according to the threshold of SPEI ≤ −1. The Statistical Downscaling Model (SDSM) was employed to downscale the meteorological variables. Drought variability under projected climate change is evaluated according to three scenarios: representative concentration pathways RCP 2.6, RCP 4.5, and RCP 8.5 using CanESM2 of the CMIP5 model for 32 years from 2019 to 2050. A drought event with maximum severity with a higher number of drought events associated with RCP 4.5 and RCP 8.5 among three scenarios, whereas synoptic stations Kanpur, Moradabad, Azamgarh, and Chitrakoot exhibit drought with higher maximum severity and frequency occurred under RCP 2.6. The Mann-Kendall (MK) test was used to assess the change in climatic variables and SPEI time series observed period. Results reveal a significant decrease in the trend of rainfall during monsoon season as well as annually observed at 16 locations except for Lucknow and Meerut and 83% of the stations exhibit a positive trend of SPEI at each timescale, which demonstrates most of the study regions exposed to the risk of drought, and locations namely Saharanpur, Meerut, and Aligarh, showed a positive trend, indicating a decrease in drying conditions over historic period. © 2023 Elsevier Ltd